High-temperature chemical strengthening method of small glass for laboratory

By increasing the temperature of glass chemical reinforcement to 700-800℃, optimizing the molten salt formula and using corundum containers and wire support, the problems of glass reinforcement difficulties and impurities in the prior art have been solved, and a more efficient and better-quality glass chemical reinforcement effect has been achieved.

CN119954413AInactive Publication Date: 2025-05-09CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510000985.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-05-09
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing laboratory chemical strengthening technology is limited by the strengthening temperature and the high temperature resistance of stainless steel containers, which leads to difficulty in strengthening low-alkali glass, poor reinforcement effect, and the contact of iron wire with salt solution leads to impurities mixing, affecting the quality of the glass.

Method used

High-temperature chemical strengthening method is used to increase the strengthening temperature to 700-800℃, optimize the molten salt formula, use corundum containers and wire support, and ensure that the iron wire does not contact molten salt throughout the entire process.

Benefits of technology

It significantly accelerates the ion exchange rate, improves the strengthening efficiency and effect, avoids the inclusion of impurities, and ensures the stability and efficiency of glass quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119954413A_ABST
    Figure CN119954413A_ABST
Patent Text Reader

Abstract

The invention relates to a high-temperature chemical strengthening method of small glass for a laboratory, which is characterized by comprising the following steps of: (1) winding the glass by using a long iron wire suspended at the upper part of a corundum boat, and immersing the lower half part of a glass sample into fused salt; (2) molten salt is added into the corundum boat wound with the iron wires, the corundum boat is put into heating equipment, the other corundum boat is covered as a cover, the temperature is increased to the strengthening temperature at the speed of 5-15 DEG C / min, and constant-temperature strengthening treatment is conducted for 0-48 h; (3) after strengthening is finished, opening a cover, pouring molten salt into the cover, hooking the sample on an iron wire bracket, and cooling and annealing along with the furnace; and finally, putting the corundum boat together with the glass sample into an ultrasonic cleaner for cleaning, and drying. The method has the advantages that by optimizing the molten salt formula, using the corundum container and the iron wire bracket and performing fine strengthening and subsequent treatment processes, the problems of molten salt volatilization, contact of iron wires with molten salt and the like caused by high temperature in the traditional method are solved, and the quality stability of the glass is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass processing and relates to a high-temperature chemical strengthening method for small-sized laboratory glass. Background Art

[0002] In the existing laboratory glass chemical strengthening technology, the glass is usually inserted into a stainless steel tempering frame and then immersed in molten potassium nitrate, sodium nitrate or their mixed molten salts for strengthening. However, this method is limited by the strengthening temperature and the high temperature resistance of the stainless steel container. The strengthening temperature usually does not exceed 500°C, resulting in a slow ion exchange rate and poor strengthening effect when processing glass with a low alkali metal content. If you try to increase the strengthening temperature, it is difficult to achieve a breakthrough due to the decomposition temperature of potassium nitrate and the high temperature resistance of the stainless steel container; at the same time, the iron wire is easily exposed to the salt solution, resulting in impurities mixing, affecting the quality of the glass. Summary of the invention

[0003] The purpose of the present invention is to make up for the shortcomings of the prior art and provide a high-temperature chemical strengthening method for small-sized laboratory glass. By increasing the strengthening temperature to within the range of 700-800°C, optimizing the molten salt formula, using a corundum container and a wire support, and a sophisticated strengthening and subsequent treatment process, the problem of difficulty in strengthening low-alkali glass in the traditional method is solved, and a more efficient and higher-quality glass chemical strengthening effect is achieved.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A high-temperature chemical strengthening method for small laboratory glass includes a corundum boat (alumina ceramics), which is characterized by using the following device: using iron wires to loosely wind around the upper and bottom of the corundum boat in a spiral shape to form an iron wire bracket, leaving enough space between the iron wires for inserting or hooking glass samples; a long iron wire is hung on the iron wire on the upper part of the corundum boat, and the long iron wire can wrap around the glass sample to ensure that only the lower half of the glass sample is immersed in molten salt, so that the iron wire does not contact the molten salt throughout the process, avoiding the mixing of impurities; The steps include: (1) Use a long wire suspended from the top of the corundum boat to wrap around the glass, ensuring that the lower half of the glass sample can be immersed in the molten salt; (2) Add molten salt to the corundum boat, place the corundum boat in a heating device, and then cover it with another corundum boat as a lid to reduce the volatilization of the molten salt due to high temperature. Heat it to the strengthening temperature (380~800℃) at a rate of 5~15℃ / min, and maintain a constant temperature for 0~48h for strengthening treatment; (3) After strengthening is completed, open the lid, turn it over and lay it flat, then pour the molten salt in the corundum boat into the lid, hook the sample on the wire bracket and cool and anneal it in the furnace to reduce thermal stress and ensure the stability of the glass quality; finally, put the corundum boat together with the glass sample into an ultrasonic cleaner for cleaning (10-30 minutes) to remove residues, and then put it into an oven for drying (drying at 110-130℃ for 50-70 minutes) to ensure the cleanliness of the glass surface.

[0005] Furthermore, the iron wire can be replaced by stainless steel wire.

[0006] Furthermore, the molten salt is potassium nitrate, sodium nitrate molten salt or a mixed molten salt.

[0007] Furthermore, the mixed molten salt is a mixed molten salt of potassium chloride and potassium carbonate or potassium sulfate.

[0008] Furthermore, the mass ratio of potassium chloride:potassium carbonate in the mixed molten salt is 2:1 or 1:1.

[0009] Furthermore, the mass ratio of potassium chloride:potassium sulfate in the mixed molten salt is 1:3.

[0010] Furthermore, when the strengthening temperature is below 500°C, potassium nitrate or sodium nitrate molten salt is used; when the strengthening temperature is between 600 and 800°C, a mixed molten salt of potassium chloride and potassium carbonate or potassium sulfate is used.

[0011] The molten salt formula of the present invention has been carefully optimized and can maintain a stable liquid state at high temperatures, providing a reliable basis for high-temperature strengthening; at the same time, the appropriate molten salt formula is selected according to different temperature ranges to further improve the strengthening effect. The use of corundum containers not only improves the high temperature resistance, but also effectively prevents the softening of materials caused by high temperature; at the same time, the chemical stability of the corundum material also ensures that it will not react with the molten salt during the strengthening process, affecting the quality of the glass. Through the fine strengthening and subsequent treatment process, the present invention successfully avoids the problems of molten salt volatilization and iron wire contacting molten salt caused by high temperature in the traditional method, ensuring the stability and efficiency of the strengthening process. The strengthening method of the present invention significantly accelerates the ion exchange rate and improves the strengthening efficiency and effect. At the same time, since the iron wire does not contact the molten salt throughout the process, the problem of impurities mixing is avoided, and the quality of the glass (such as strengthening temperature and stability) is further improved. The present invention provides an efficient and reliable new way for high-temperature chemical strengthening of small glass for laboratory use.

[0012] Beneficial effects of the present invention: Compared with the prior art, the present invention successfully increases the strengthening temperature of glass to 700-800°C by optimizing the molten salt formula, innovatively using corundum containers and iron wire brackets, and sophisticated strengthening and subsequent treatment processes, achieving a dual improvement in strengthening effect and efficiency. At the same time, the present invention also solves the problems of molten salt volatilization and iron wire contact with molten salt caused by high temperature in traditional methods, ensuring the quality stability of the glass. The present invention not only has significant technical advancement and practical value, but is also expected to have a positive impact in the field of glass processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a schematic diagram of a high-temperature chemical strengthening device for small-sized glass used in a laboratory, wherein 1 is a corundum boat containing molten salt, 2 is an iron wire, 3 is a cover of the corundum boat, 4 is a glass sample, 5 is a long iron wire for fixing the sample, and 6 is an iron wire hook. DETAILED DESCRIPTION

[0014] Combine the following Figure 1 , the present invention is further described: A high-temperature chemical strengthening device for small-sized glass in a laboratory comprises two corundum boats (alumina ceramics, rectangular in size of 150*50*50mm) 1 of the same size, one of which is used as a lid; iron wires (diameter 1mm) 2 are loosely wound in a spiral shape on the upper and bottom of the corundum boat to form an iron wire bracket, and sufficient space is left between the iron wires for hooking a glass sample 4; a long iron wire 5 is hung on the upper iron wire of the corundum boat through a wire hook 6, and the long iron wire can be wound around the glass sample 4 to ensure that only the lower half of the glass sample is immersed in molten salt, so that the iron wire does not contact the molten salt throughout the process to avoid impurities from mixing.

[0015] A high temperature chemical strengthening method for small laboratory glass, the specific implementation steps are as follows: Example

[0016] (1) Add 10 g of mixed molten salt (the mass ratio of potassium chloride to potassium carbonate is 1:1) into the corundum boat, place the corundum boat in a muffle furnace and cover it with another corundum boat as a lid to reduce the volatilization of the molten salt due to high temperature. Raise the temperature to the strengthening temperature of 650 °C at a rate of 10 °C / min (during this process, the temperature and state of the molten salt must be continuously monitored to ensure that it is completely melted and remains in a stable liquid state); (2) After reaching the strengthening temperature, put the glass sample into the furnace for preheating for half an hour, take it out and wrap the glass with a long iron wire, and then hang it on the wire bracket on the upper part of the corundum boat, ensuring that the lower half of the glass sample can be immersed in the molten salt; cover it with a lid and maintain a constant temperature for 1 hour for strengthening treatment; (3) After strengthening is completed, the corundum boat is taken out of the muffle furnace, the lid is opened, and the lid is turned over and laid flat. Then, the molten salt in the corundum boat is poured into the lid to cool. The corundum boat containing the glass sample is placed in an annealing furnace at 600°C for furnace cooling and annealing to eliminate thermal stress and ensure stable glass quality. (4) After annealing, place the corundum boat and the glass sample in an ultrasonic cleaner and clean them with a cleaning agent (alcohol) for 20 min. Then place them in an oven and dry them at 120 °C for 60 min. Example

[0017] (1) Add 10 g of mixed molten salt (the mass ratio of potassium chloride to potassium sulfate is 1:1) into the corundum boat, place the corundum boat in a muffle furnace and cover it with another corundum boat as a lid to reduce the volatilization of the molten salt due to high temperature. Raise the temperature to the strengthening temperature of 750 °C at a rate of 12 °C / min (during this process, the temperature and state of the molten salt must be continuously monitored to ensure that it is completely melted and remains in a stable liquid state); (2) After reaching the strengthening temperature, put the glass sample into the furnace for preheating for half an hour, take it out and wrap the glass with a long iron wire, and then hang it on the wire bracket on the upper part of the corundum boat, ensuring that the lower half of the glass sample can be immersed in the molten salt; cover it with a lid and maintain a constant temperature for 1.5 hours for strengthening treatment; (3) After strengthening is completed, the corundum boat is taken out of the muffle furnace, the lid is opened, and the lid is turned over and laid flat. Then, the molten salt in the corundum boat is poured into the lid to cool. The corundum boat containing the glass sample is placed in an annealing furnace at 700°C for furnace cooling and annealing to eliminate thermal stress and ensure stable glass quality. (4) After annealing, place the corundum boat and the glass sample in an ultrasonic cleaner and clean them with a cleaning agent (alcohol) for 15 min. Then place them in an oven and dry them at 120 °C for 60 min. Example

[0018] (1) Add 12 g of mixed molten salt (the mass ratio of potassium chloride to potassium carbonate is 2:1) into the corundum boat, place the corundum boat in a muffle furnace and cover it with another corundum boat as a lid to reduce the volatilization of the molten salt due to high temperature, and heat it to the strengthening temperature of 750 °C at a rate of 8 °C / min (during this process, the temperature and state of the molten salt must be continuously monitored to ensure that it is completely melted and remains in a stable liquid state); (2) After reaching the strengthening temperature, put the glass sample into the furnace for preheating for half an hour, take it out and wrap the glass with a long iron wire, and then hang it on the wire bracket on the upper part of the corundum boat, ensuring that the lower half of the glass sample can be immersed in the molten salt; cover it with a lid and maintain a constant temperature for 2 hours for strengthening treatment; (3) After strengthening is completed, the corundum boat is taken out of the muffle furnace, the lid is opened, and the lid is turned over and laid flat. Then, the molten salt in the corundum boat is poured into the lid to cool. The corundum boat containing the glass sample is placed in an annealing furnace at 650°C for furnace cooling annealing to eliminate thermal stress and ensure stable glass quality. (4) After annealing, place the corundum boat and the glass sample in an ultrasonic cleaner and clean them with a cleaning agent (alcohol) for 20 min. Then place them in an oven and dry them at 120 °C for 60 min.

Claims

1. A high temperature chemical strengthening method for small laboratory glass, comprising a corundum boat, characterized in that The following device is used: iron wires are loosely wound around the upper and bottom of the corundum boat in a spiral shape to form an iron wire bracket, and sufficient space is left between the iron wires for inserting or hooking the glass sample; a long iron wire is hung on the iron wire on the upper part of the corundum boat, and the long iron wire can wrap around the glass sample to ensure that only the lower half of the glass sample is immersed in the molten salt; The steps include: (1) Use a long wire suspended from the top of the corundum boat to wrap around the glass, ensuring that the lower half of the glass sample can be immersed in the molten salt; (2) Add molten salt to the corundum boat, place the corundum boat in a heating device, cover it with another corundum boat as a lid, heat it to a strengthening temperature of 380-800°C at a rate of 5-15°C / min, and maintain the strengthening treatment at a constant temperature for 0-48h; (3) After strengthening is completed, open the lid, turn it over and lay it flat, then pour the molten salt in the corundum boat into the lid, hook the sample on the wire bracket and cool and anneal in the furnace; finally, put the corundum boat together with the glass sample into an ultrasonic cleaner for cleaning, and then put it into an oven for drying.

2. A high temperature chemical strengthening method for small laboratory glass according to claim 1, characterized in that: The iron wire can be replaced by stainless steel wire.

3. A high temperature chemical strengthening method for small laboratory glass according to claim 1, characterized in that: The molten salt is potassium nitrate, sodium nitrate molten salt or mixed molten salt.

4. A high temperature chemical strengthening method for small laboratory glass according to claim 3, characterized in that: The mixed molten salt is a mixed molten salt of potassium chloride and potassium carbonate or potassium sulfate.

5. A high temperature chemical strengthening method for small laboratory glass according to claim 4, characterized in that: The mass ratio of potassium chloride to potassium carbonate in the mixed molten salt is 2:1 or 1:

1.

6. A high temperature chemical strengthening method for small laboratory glass according to claim 4, characterized in that: The mass ratio of potassium chloride to potassium sulfate in the mixed molten salt is 1:

3.

7. A high temperature chemical strengthening method for small laboratory glass according to any one of claims 1 to 6, characterized in that: When the strengthening temperature is below 500°C, potassium nitrate or sodium nitrate molten salt is used; when the strengthening temperature is between 600 and 800°C, a mixed molten salt of potassium chloride and potassium carbonate or potassium sulfate is used.

8. A high temperature chemical strengthening method for small laboratory glass according to any one of claims 1 to 6, characterized in that: The drying conditions in step (3) are 110-130° C. for 50-70 min.

Citation Information

Patent Citations

  • Process and device for the production of curved and toughened glass panes

    AT283630B

  • Hanging type chemical enhancement method for glass with thickness of 0.3 mm to 2 mm

    CN102674674A

  • Ultra-thin flexible glass toughening process and equipment for improving appearance defects

    CN113461343A

  • Method for preparing high-purity iron through high-temperature fused salt electrodeposition

    CN114232033A

  • Method and apparatus for strengthening glass

    CN1795149A